Building a strong ummah: Muslim women in the Twenty-first century - Hossen, Belayet; Osmani, Noor Mohammad (International Institute for Muslim Unity, IIUM, 2019)
This paper argues that women are an essential part of society like men and both male and female are complementary to each other. In Islam, besides a male’s role, a female’s role also is significant to build a sound and a strong Ummah. A mother plays her role inside a family, performs her roles and responsibilities towards her husband and children. She has the potentials and qualities to contribute for the larger community as a whole. She is not isolated from the community affairs in Islamic society. Rather, she should offer her skills and knowledge in the advancement of society. This paper illustrates how a woman can play a crucial role as an ideal mother, ideal wife, ideal educator, ideal medical doctor and an ideal leader as they played in the earlier period of Islam. Khadījah R.A. (may Allah swt be pleased with her), the first wife of the Prophet Muhammad (pbuh) was a successful businesswoman. His youngest wife, ‘Ayishah (r.a.) led the battlefield in a battle called ‘×arb al-Jamal’ [battle of camel]. During the reign of Caliph ʻUmar (r.a), he appointed a woman as an invigilator for monitoring a market. This paper asserts that if Muslim women are fostered properly, they would be able to immensely contribute towards building a strong Muslim community as they did during the time of the Prophet Muhammad (pbuh).